IMPROVING MECHANISMS FOR ENSURING THE FINANCIAL STABILITY OF ENERGY ENTERPRISES IN THE DIGITAL TRANSFORMATION - Shoira Bo’ranbayeva (Modern American Journals, 2026)
Digital transformation is reshaping the strategic, operational, and financial models of energy enterprises worldwide. The integration of digital technologies—IoT, AI, smart grids, predictive analytics, blockchain—creates new opportunities to improve financial sustainability but also introduces new risks. This paper explores mechanisms for improving financial stability in energy companies during digitalization. This study examines how digital transformation reshapes the financial stability mechanisms of energy enterprises operating in increasingly volatile global markets. Through a combination of literature synthesis, quantitative analysis of international energy-sector indicators, and assessment of digital technology adoption trends, the research identifies key drivers of financial resilience, including predictive analytics, smart grid technologies, digital-twin modeling, and cybersecurity systems. Findings show that enterprises with higher digital maturity exhibit stronger operational efficiency, improved cost structures, and reduced exposure to market and technological risks. The paper proposes an integrated financial-stability framework that aligns digital investments with risk management, strategic planning, and performance monitoring.
Keywords: IoT in energy; AI-driven forecasting; digital finance systems; energy market volatility; asset optimization; data analytics; cyber resilience; distributed energy resources; digital investment strategies.